Characteristics Of Head Injured Patients : Literatur Review - Sasya Zulian Nurfalah; Reeny Purnamasari Juhamran; Muhammad Fadli Said (Sean Institute, 2024)
According to the World Health Organization (WHO) report, every year around 1.2 million people die diagnosed with serious head injuries, namely as a result of traffic accidents (KLL). Head injuries are one of the leading causes of death and disability worldwide. The study of the characteristics of patients with head injuries is an important aspect in efforts to better understand this condition and improve patient management and care. The aim of this literature review is to determine the characteristics of head injuries in patients. The research method used in this research is Literature Review or literature review. The keywords used are